Aluminum Resistance Transcription Factor 1(ART1) contributes to natural variation in aluminum resistance indiverse genetic backgrounds of rice (O. sativa) - Arbelaez, Juan D.; Maron, Lyza G.; Jobe, Timothy O.; Piñeros, Miguel A.; Famoso, Adam N.; Rebelo, Ana Rita; Singh, Namrata; Ma, Qiyue; Fei, Zhangjun; Kochian, Leon V.; McCouch, Susan R. (Wiley, 2017)
Transcription factors (TFs) regulate the expression of other genes to indirectly mediate stress resistance mechanisms. Therefore, when studying TF‐mediated stress resistance, it is important to understand how TFs interact with genes in the genetic background. Here, we fine‐mapped the aluminum (Al) resistance QTL Alt12.1 to a 44‐kb region containing six genes. Among them is ART1, which encodes a C2H2‐type zinc finger TF required for Al resistance in rice. The mapping parents, Al‐resistant cv Azucena (tropical japonica) and Al‐sensitive cv IR64 (indica), have extensive sequence polymorphism within the ART1 coding region, but similar ART1 expression levels. Using reciprocal near‐isogenic lines (NILs) we examined how allele‐swapping the Alt12.1 locus would affect plant responses to Al. Analysis of global transcriptional responses to Al stress in roots of the NILs alongside their recurrent parents demonstrated that the presence of the Alt12.1 from Al‐resistant Azucena led to greater changes in gene expression in response to Al when compared to the Alt12.1 from IR64 in both genetic backgrounds. The presence of the ART1 allele from the opposite parent affected the expression of several genes not previously implicated in rice Al tolerance. We highlight examples where putatively functional variation in cis‐regulatory regions of ART1‐regulated genes interacts with ART1 to determine gene expression in response to Al. This ART1–promoter interaction may be associated with transgressive variation for Al resistance in the Azucena × IR64 population. These results illustrate how ART1 interacts with the genetic background to contribute to quantitative phenotypic variation in rice Al resistance.